2016
DOI: 10.1519/jsc.0000000000001232
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning and Placebo Intervention Improves Resistance Exercise Performance

Abstract: This study evaluated the effect of ischemic preconditioning (IPC) on resistance exercise performance in the lower limbs. Thirteen men participated in a randomized crossover design that involved 3 separate sessions (IPC, PLACEBO, and control). A 12-repetition maximum (12RM) load for the leg extension exercise was assessed through test and retest sessions before the first experimental session. The IPC session consisted of 4 cycles of 5 minutes of occlusion at 220 mm Hg of pressure alternated with 5 minutes of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(122 citation statements)
references
References 37 publications
9
107
1
5
Order By: Relevance
“…Portanto, análises mais holísticas 28,30 e específicas ao subtipo de modalidade [31][32][33][34][35] são desejáveis. Outro ponto ressaltado em alguns estudos é que o efeito do IPC poderia ter base motivacional 18,20 , visto que alguns deles mostram que a aplicação da manobra de IPC repetidas vezes minimiza o desempenho físico 19,36 ao longo do tempo. O efeito placebo, altamente reconhecido em estudos sobre o desempenho humano 37 , portanto, precisa ser controlado e considerado na interpretação e tomada de decisão sobre qualquer estratégia 19,25 .…”
Section: Métodos De Investigação E Interpretação Dos Resultadosunclassified
See 1 more Smart Citation
“…Portanto, análises mais holísticas 28,30 e específicas ao subtipo de modalidade [31][32][33][34][35] são desejáveis. Outro ponto ressaltado em alguns estudos é que o efeito do IPC poderia ter base motivacional 18,20 , visto que alguns deles mostram que a aplicação da manobra de IPC repetidas vezes minimiza o desempenho físico 19,36 ao longo do tempo. O efeito placebo, altamente reconhecido em estudos sobre o desempenho humano 37 , portanto, precisa ser controlado e considerado na interpretação e tomada de decisão sobre qualquer estratégia 19,25 .…”
Section: Métodos De Investigação E Interpretação Dos Resultadosunclassified
“…Ressaltamos que, apesar da "explosão" de publicações científicas sobre IPC e desempenho ocorrer a partir do estudo de Libonati e seus colegas em 2001, na verdade desde 1958 fisiologistas Alemães testaram o IPC como recursos ergogênico potencial e encontraram resultados controversos 8 . Porém, considerando a partir do "de novo" de Libonati e colaboradores, estudos relatam melhoria ou nenhum efeito agudo do IPC sobre o desempenho em atividades como ciclismo 17 , sprints, natação 18 , treinamento resistido 19,20 , futebol 21 e remo em apneia 22 . Também surgiram trabalhos tentando verificar efeito ergogênico do IPC sobre o processo de recuperação do desempenho 7,23,24 , com achados igualmente inconclusivos.…”
Section: História Do Ipc E Suas Aplicações Ao Desempenhounclassified
“…Furthermore, the authors reported that the number of repetitions during elbow flexion exercise significantly increased in the early sets, but they tended to decrease over four trials 25) . These two studies suggest that IPC has minor beneficial effects, but these apparently fade over time and may possibly have a placebo effect because, compared with control (CON), the SHAM condition also improved repetitions along with IPC 24,25) . Beaven et al (2012) compared the early (immediate) and late (24 h later) effects of IPC on power production, and they found that IPC showed beneficial effects in both periods 8) .…”
Section: Sprint (Cycle) Performancementioning
confidence: 95%
“…For example, IPC prolonged the time to failure during rhythmic handgrip at an intensity of 45% of maximal voluntary contraction (MVC) 23) . Marocolo et al (2016a) also reported that IPC and SHAM conditions resulted in significantly greater repetitions versus the control condition on the first and second sets, but not on the third set during leg extension at a 12 RM load 24) . Furthermore, the authors reported that the number of repetitions during elbow flexion exercise significantly increased in the early sets, but they tended to decrease over four trials 25) .…”
Section: Sprint (Cycle) Performancementioning
confidence: 97%
“…Com o número de estágios realizados, calculamos a distância total percorrida para cada futebolista. Com o propósito de evitar quaisquer efeitos placebo ou nocebo, comuns em estudos com testes de desempenho físico 23,24 as jogadoras não foram informadas sobre o real objetivo do presente trabalho. Apenas foi ressaltado que o objetivo era realizar o melhor desempenho possível nos testes.…”
Section: Yoyo Intermitente Endurance Nível 2 (Yoyoie2)unclassified